2000
DOI: 10.1017/s0029665100000070
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting newborn bone mineral content:in uteroeffects on newborn bone mineralization

Abstract: 55Abbreviations: AGA, appropriate-for-gestational age; BMC, bone mineral content; BMD, bone mineral density; ICTP, cross-linked carboxy-terminal telopeptide of type I collagen; IDM, infants of diabetic mothers; 1, Recently, we found evidence of decreased bone formation rates in infants who were small-for-gestational age (SGA) compared with infants who were appropriate-forgestational age; we reported reduced BMC, cord serum osteocalcin (a marker of bone formation) and 1,25-dihydroxyvitamin D (the active metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 79 publications
4
55
0
1
Order By: Relevance
“…18,19 The present study adds to this knowledge the fact that after accounting for these variables, infant BMC is positively associated with infant vitamin D status. Therefore, larger infants will have greater BMC only if they have adequate vitamin D. The inverse relation between infant BMC and maternal vitamin D concentration observed in the regression analysis, after accounting for infant gestational age, weight and vitamin D status at birth, is new and difficult to explain.…”
Section: Discussionmentioning
confidence: 66%
“…18,19 The present study adds to this knowledge the fact that after accounting for these variables, infant BMC is positively associated with infant vitamin D status. Therefore, larger infants will have greater BMC only if they have adequate vitamin D. The inverse relation between infant BMC and maternal vitamin D concentration observed in the regression analysis, after accounting for infant gestational age, weight and vitamin D status at birth, is new and difficult to explain.…”
Section: Discussionmentioning
confidence: 66%
“…These findings confirm published data reporting a reduced bone mineral density in SGA compared with AGA infants measured by X-ray absorptiometry and DXA. 37,38 Two studies using tibial speed of sound reported higher QUS values for SGA compared with AGA infants, which might, however, be explained by a soft-tissue effect that none of the working groups corrected for. 16,17 The main cause of osteopenia of prematurity is the postnatally reduced supply of calcium, phosphate and vitamin D. Several studies provide evidence that an increased supply of these substances can improve bone mineral density during the neonatal period as measured by photonabsorption densitometry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that altered bone mineralization, which is known to be a consequence of IUGR (39), could have made the ribs more compliant. Whatever the causes of the increase in C W , the effects were still evident at 8 wk and likely would have persisted beyond this age.…”
Section: Discussionmentioning
confidence: 99%